POLSTRACC F14 ICECREAM ... - Haenel, Florian; Johansson, Sören; Woiwode, Wolfgang; Höpfner, Michael (Institute of Meteorology and Climate Research, Atmospheric Trace Gases and Remote Sensing (IMK-ASF), Karlsruhe Institute of Technology (KIT), 2021)
The data set presented here consists of a case study in the framework of the DFG-project ICECREAM (Analysis of high-latitude cirrus cloud feedbacks on the trace gas composition of the UTLS), and comprises observations of the trace gases water vapour (H2O), ozone (O3), nitric acid (HNO3) and clouds in the upper troposphere/lowermost stratosphere (UT/LMS) by the infrared remote sensing instrument GLORIA (Gimballed Limb Observer for Radiance Imaging of the Atmosphere), and the corresponding model data of dedicated simulations with the numerical weather prediction (NWP)-model ICON (ICOsahedral Nonhydrostatic) with the extension ART (Aerosols and Reactive Trace gases), and the chemistry-climate model (CCM) EMAC (ECHAM5/MESSy Atmospheric Chemistry). The data cover one research flight during the Arctic winter 2015/2016, when GLORIA was deployed on-board the German Research aircraft HALO (High Altitude and LOng range research aircraft) during the POLSTRACC (POLar STRAtosphere in a Changing Climate), GW-LCYCLE ... : HALO GLORIA ...